PENGARUH KUALITAS LAYANAN DAN HARGA JASA PENGIRIMAN BARANG TEHRADAP KEPUASAN PELANGGAN PT PUTRA NUSA TRANSPORTINDO - Alfajri Gita Ramadhan; Muhammad Harri (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
The purpose of this study was to analyze the effect of service quality and price on customer satisfaction of PT Putra Nusa Transportindo. This research method uses filling and distributing questionnaires using a Likert scale. The analysis method uses multiple and simple regression. Based on the results of the analysis, it shows that in multiples or simply, service quality and price have a positive and significant effect on customer satisfaction at PT PutraNusa Transportindo.